Student Opinion about Beauty Clinics in Jember Regency - Alviah, Imas Kusnul; Juariyah, Juariyah (Sciences and Clinical Pharmacy Research Journal, 2024)
It is known that students are passionate about some of the best clinics in Jember Regency, including Larissa Aesthetic Center, KSC Beauty Clinicque, and Naavagreen. It is the purpose of this study to find out where students get information about beauty clinics, what students think about beauty clinics in Jember Regency, and what problems students face when going to beauty clinics. This study used S-O-R (Stimulus-Organism-Response) theory and conducted case studies at three beauty clinics: Navagreen, Kartika Skin Care Beauty Clinique, and Larissa Aesthetic Center. Purposive sampling method was used to select informants in this study. Studies show that students get information about beauty clinics through Instagram social media and recommendations from their friends and family. Students consider beauty clinics as facials. College students believe that beauty clinics are places for facials, and nowadays, facials are important for college students. There are several issues college students face, including unfriendly customer service and the lack of information doctors provide about their symptoms after treatment. Thus, it can be concluded that students get more information about beauty clinics in Jember Regency through Instagram social media. Most students' opinions about beauty clinics are that they have a positive impact for those who want to take care of their health.